PROGRAM PENGHIJAUN KAMPUS SEBAGAI STRATEGI UNTUK MENINGKATKAN KEBERSIHAN DAN KEBERLANJUTAN LINGKUNGAN - Sulani, Sulani; Nur Afiyah, Safitri; Suwito, Suwito; Sarwo, Sarwo; Sudja’i, Sudja’i (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This study aims to evaluate the effectiveness of greening activities at Universitas Sunan Giri Surabaya as a strategic effort to improve campus cleanliness and environmental sustainability. The study employed the Asset Based Community Development (ABCD) approach, positioning students as the main actors who utilized available assets and potentials to support program implementation. Data were collected through field observations and activity documentation. The results indicate that the greening activities successfully enhanced campus environmental quality, increased students’ awareness and concern for cleanliness, and strengthened collaboration among the academic community. In addition to ecological benefits such as healthy plant growth and improved microclimate conditions, the program also served as an effective medium for environmental education and character building. Therefore, campus greening is proven to be an effective strategy for fostering a culture of cleanliness and sustainability and can be replicated continuously to ensure long-term positive impacts.